Polifonia e dialogismo Bakhtiano na festa dos Lambe-Sujos e Caboclinhos de Laranjeiras/SE - Silva, Wagner Guimarães (2012)
The objective of this dissertation is to analyze the popular party of dirty-Lambe and caboclinhos city Laranjeiras through a bias-discursive language, using it for the articulation between different areas of knowledge, such as the very language, history the collective memory and discourse analysis. Aiming to establish new counterpoints to monologic discourse than would be the party to that community, as well as trying to identify under festive two concepts used by Russian thinker Mikhail Bakhtin, who would dialogism and polyphony. The study was based on the observation that during the party, which is the war between two distinct ethnic groups, which would be known as blacks lick dirty and the Indians called caboclinhos. During the encounter, not only physical, but also discursive both groups waging a struggle dialogical, which brings up the concepts coined by Bakhtin, dialogism and polyphony, which rest in a universe where the inversion takes account of the life of brincantes, resuming another concept that can not be discarded in this study, which would be carnivalization bakhtininiana. The investment in relation to the openness of brincantes during the celebration and reception of the public promoting dialogism and polyphony desired, with the inclusion of otherness discourse, and the expressions of the views of the spectators, reinforcing the notion of a collective identity for that community, conveyed through the feast of dirty-Lambe and Caboclinhos. The text explains and reflects on the discursive universe that opens during the presentation of groups, finally proving the hypothesis of work. In short, when it comes to results on the proposed topic, it appears that the party promotes an annual turnover and continuous construction and reconstruction of identity made possible by the roles played by the party brincantes, who converted to participants and / or interactors, cumulatively renew , expand and problematize the notion of identity through a popular festival like the one in question.